Texture + materials - Gagg, Russell (Lausanne ; Worthing : AVA Academia, 2012)
Introduction. Stone, brick and concrete: History and context; International icons; Sustainability; Innovations and the future. Metals: History and context; International icons; Sustainability; Innovations and the future. Wood: History and context; International icons; Sustainability; Innovations and the future. Glass: History and context; International icons; Sustainability; Innovations and the future. Plastics: History and context; International icons; Sustainability; Innovations and the future. Composites: History and context; International icons; Sustainability; Innovations and the future. Tiles: History and context; International icons; Sustainability. Conclusion. Glossary. Resources. Index. Acknowledgements. Working with ethics.
boek